Development of Predictive Index for Default Treatment At Multibacillary Leprosy in District Sampang - Muhammad Syarif Rukua; Santi Martini; Hari Basuki Notobroto (Jurnal Berkala Epidemiologi, 2015)
The default treatment is related to the patient's regularity in taking medication. Irregular drug consumption, the leprosy bacteria can become resistant or immune to Multi-Drug Therapy. The purpose of this study was to determine the indicators and formulate a predictive index formula for the default incidence of leprosy treatment. This study uses a case-control design. The sample size in this study was 62 respondents. The sampling technique uses a simple random sampling technique. Data collection techniques were carried out with interviews with the help of questionnaires. The results showed that the variables that became indicator candidates (p <0.25) were income (p = 0.013), access to health services (p = 0.022), the role of health workers (p = 0.032), knowledge (p = 0.001), and family support (p = 0.023), perception of disease (p = 0.098), leprosy reaction (p = 0.198). The seven variables are indicators of the incidence of leprosy treatment defaults, namely the role of health workers, family support, knowledge, and income. Formula predictive index of the default occurrence of treatment of people with leprosy type multibacilary is (-1,666 + 1,451 * Income (low) + 1,989 * Role of Health Officers (less involved) + 1,338 * Knowledge (less) + 1,543 * Family Support (less support)). This index has an accuracy rate of 79%. This index is expected to be used as a measurement tool to help health workers in screening leprosy patients who are currently undergoing treatment, so that early on it can be known which sufferers have the potential to default treatment.